Pengaruh Brand Awareness dan Perceived Quality Terhadap Brand Trust Produk Sports Nutrition Biotechusa di Indonesia - Tantio Dipo Priantono; Muhammad Saleh Afief (MES Management Journal, 2026)
This study aims to analyze the influence of Brand Awareness and Perceived Quality on Brand Trust in BiotechUSA sports nutrition products in Indonesia. The research employed a quantitative descriptive approach using purposive sampling techniques. Respondents consisted of consumers who had known, used, or purchased BiotechUSA products. Primary data were collected through an online questionnaire distributed using Google Forms. Data analysis was conducted using Partial Least Square Structural Equation Modeling (PLS-SEM) with SmartPLS software. The findings indicate that Brand Awareness has a positive effect on Brand Trust. In addition, Brand Awareness positively influences Perceived Quality. The study also reveals that Perceived Quality has the strongest positive effect on Brand Trust among all variables examined. These findings suggest that consumers' perception of product quality plays a crucial role in building trust toward sports nutrition brands.